Incidents reporting: barriers and strategies to promote safety culture - Fabiana Rossi Varallo; Aline Cristina Passos; Tales Rubens de Nadai; Patricia de Carvalho Mastroianni (SciELO, 2018)
ABSTRACT Objective The purpose was to identify the barriers of underreporting, the factors that promote motivation of health professionals to report, and strategies to enhance incidents reporting. Method Group conversations were carried out within a hospital multidisciplinary team. A mediator stimulated reflection among the subjects about the theme. Sixty-five health professionals were enrolled. Results Complacency and ambition were barriers exceeded. Lack of responsibility about culture of reporting was the new barrier observed. There is a belief only nurses should report incidents. The strategies related to motivation reported were: feedback; educational intervention with hospital staff; and simplified tools for reporting (electronic or manual), which allow filling critical information and traceability of management risk team to improve the quality of report. Conclusion Ordinary and practical strategies should be developed to optimize incidents reporting, to make people aware about their responsibilities about the culture of reporting and to improve the risk communication and the quality of healthcare and patient safety.